Down to earth managing soil degradation in agricultural lands of Lucena City using Nature-based solutions - De Guzman, Tyrone
This thesis investigates soil degradation in the agricultural lands of a lowland agriculture-dependent community in the Philippines and proposes Nature-Based Solutions as a means of managing soil degradation. Lucena City was chosen as it continues to have a large dependence on agricultural land that feed the city and from where many resident's livelihoods depends on. Even if agriculture plays a big role in the city, many residents and farmers to not conduct soil testing or adopt soil heath management techniques. By adopting nature-based solutions, the farmers could have a way to maintain soil health and prevent soil degradation. The research methodology starts by identifying the social and physical aspects of soil degradation through conducting biotope mapping, soil sampling, and numerous interviews with farmers, farmer leaders, and the city agriculturalist. After, key informant interviews along with an extensive literature review were conducted to identify Nature-Based Solutions (NbS) which addresses the identified problems of soil degradation in Lucena. Three possible future scenarios were identified to project what can happen in the future due to the finding of soil degradation in Lucena. These scenarios are: "Business as usual", "Use Only Organic Fertilizer", and "Use Nature-Based Solutions". After an inclusive soil heath assessment where the study determines which scenario is best by considering both the farmers and degree of soil degradation, the nature-based solution scenario was determined to be the case study that would be pursued. The study proposed zones, interventions, and techniques using nature-based solutions in two sited based on having the worst soil degradation in the rice fields sampled. A masterplan was designed using nature-based solutions in these two sites representing an ideal rice farm which maintains soil health from where a comprehensive soil health management plan was developed. By using nature-based solutions to address soil health, the study promotes more sustainable forms of agriculture in where maintaining soil health is synonymous with feeding our growing population.